Research progress on the molecular mechanism of red color formation in peach fruit - GUO Tianfa; QIU Qianqian; DU Mo; MA Xiaofeng; WU Cuiyun (Guoshu xuebao)
The peach Prunus persica (Rosaceae) is an important deciduous fruit tree native to China, where many wild varieties provide excellent genetic resources for peach-breeding programs. Colors of these varieties vary widely including reds, yellows, greens, and whites. Of them, red color is generated mainly by accumulation of anthocyanin, a natural water-soluble pigment that occurs widely in plants. The color of anthocyanin varies depending on pH, temperature and other conditions. The pigment also has medicinal properties such as prevention of cardiovascular disease, relieving vision, and enhancing immunity. The greater the anthocyanin content, the deeper the red color. When the fruit is green, white or yellow, anthocyanin contents are low. The common anthocyanin pigments in peach are primarily cyanindin and elargonidin, and secondarily delphinidin, peonidin, petunidin, and malvidin. Anthocyanin synthesis is mainly affected by genetics, with PpMYB10.1 serving as the key transcription factor in peach. However, synthesis is also affected by light, temperature, hormones, sugar, and mineral elements. Anthocyanin plays an important role in people's health, and studies on red color production in peach fruit benefits breeding programs. While China's first early maturity and low-acid red-fleshed peach variety Jinling xuepan has taken China's peach-breeding research to a new level. However, further enriching the diversity of peach fruit color should also be considered in breeding programs. In this paper, we review the studies on genetic variation and regulatory mechanisms related to formation of red color in peach pericarp and pulp to improve the identification of genotypes affecting peach fruit color, and innovation in peach-red-germplasm in breeding programs.